Analisis Faktor Penyebab Keengganan Siswa dalam Bertanya dan Berpendapat Pada Proses Pembelajaran di Kelas: Kajian Literatur - Miftahul Jannah; Rosdialena R (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Student reluctance to ask questions and express opinions in class is a phenomenon that frequently occurs in the learning process, yet the underlying factors are not yet fully understood. This study aims to analyze the factors that cause students to be reluctant to ask questions and express opinions during classroom learning. The method used is a literature study, conducted by collecting, reading, comparing, and analyzing scientific journal articles relevant to the topic. The results show that student reluctance to ask questions and express opinions is caused by two groups of factors, namely internal factors including low self-confidence, lack of understanding of the material, and limited language ability, as well as external factors including an unsupportive classroom environment, suboptimal teacher roles, and negative social pressure from peers. Both factors are interrelated and mutually reinforcing. This study is expected to increase the awareness of teachers, parents, and schools toward students experiencing these factors, so that appropriate interventions can be taken to create a more active and participatory learning environment.